Measuring productivity in manufacturing sector - Balakrishnan, Pulapre (2004)
Conventional wisdom and current practice in India appear to privilege total factor productivity (TFP), as a measure of productivity, rather than labour productivity. However, labour productivity is a measure of potential consumption and, as such, a leading claimant for the indicator of standard of living, which makes it important in any programme of poverty reduction. Estimates of labour productivity also give us useful additional information in evaluating the reforms undertaken in India in the 1990s. - Reproduced.
Keywords: Productivity; Manufacturing industry; Labour productivity